Разработка модели влияния изменения параметров теплоносителя и рабочего вещества на паропроизводительность парогенераторов ПГВ-1000 энергоблоков АЭС с ВВЭР-1000 - Потанина, Татьяна Владимировна; Ефимов, Александр Вячеславович (НТУ "ХПИ", 2007)
The regression model construction describing of steam generator PGV-1000 charge pair dependence from thermal and hydraulic parameters is considered. In model influences on charge pair parameters, also their interactions are taken into account
Keywords: энергетика; энергообъекты; паропроизводительность; теплоноситель